Universities and tweeting: a content analysis of collegiate tweets - Urban, Ryan (Kansas State University, 2021)
Universities promote themselves on Twitter for a number of reasons: increase enrollment, promote the institution’s programs, and more. However, while research has dictated what universities tweet about, research has not yet determined what the most popular topical frames are that universities tweet. This study utilizes a content analysis to determine the most popular topical frames, the correlation between engagements and engaging elements on university Twitter accounts, and what the “balancing act” is that universities perform in tweeting about controlled and uncontrolled events such as a new facility opening, vs something such as the COVID-19 pandemic. Results indicate that tweets are monologic, most likely to post about academics such as research projects (without naming the researcher(s) in the tweets) and controlled subjects such as research, rather than uncontrolled subjects like scandals. In addition, the engaging elements such as visuals, hashtags, and polls do not appear to uphold traditions of driving engagements, instead only user comments on university tweets appear to be boosting engagements.
Keywords: Twitter; Framing theory; University tweets; Engaging elements